Testosterone and Gonadotropins in Infertile Men with Sertoli Cell Only Syndrome from Gaza Strip (Journal of Medicine, 2017)
Aim: To assess serum testosterone and gonadotropins in Sertoli cell only syndrome patients from Gaza Strip.Methods: Based on testicular biopsy, a cross section of 74 Sertoli cell only syndrome patients were enrolled in the study. Age matched 44 fertile men were served as controls. Patients and controls were questioned for their medical history. Blood samples were drawn and serum testosterone, luteinizing hormone (LH), and follicle stimulating hormone (FSH) were determined by enzyme-linked immunosorbent assay. Data were computer analyzed using SPSS/PC, version 18.0.Results: Varicocele and hormonal problems were significantly more frequent among patients than controls (P